Uma criação em processo: Ignácio de Loyola Brandão e Não verás país nenhum - Salles, Cecilia Almeida (1990)
The objectiveaf this researchis to understand the artistic process of creation trying to eliminate the mystic cloud in which this process is almost always involved. We have analysed, specifically, the process thraugh which Ignácio de Loyola Brandão has gane through to reach the production af his book "Não Verás País Nenhum". Our starting point for this analysis was the observation of the concrete footsteps af the process left by the writer - i.e. the diaries, notes, drafts, photographs, maps and newsoaper articles the writer made use to write his novel. We have also appealed to the theory about the creative process provided by the creators of different artistic manifestations through interviews, testimonies, poetics and also through some of their own works that are sometimes real theoretical treatises. We have adopted the semiotic theory of Charles Sanders Peirce as the theoretical framework for this analysis. His abstract, general and formal concepts worked as tools of investigation for the production af singular concepts that revealed how the concrete sign system we had in hand operated. The thesis is divided into four chapters. In the first two chapters, the more general characteristies of the process of creation are analysed. In Chapter I, this process is analysed as a complex path towards an aim - a process of final causation; in Chapter II, we discuss the manifestation, in the creative process, of the continuation of the literary sign through the presence of the future readers - the creation as a communicative act. We have analysed, in the other chapters, more specific aspects of the prccess of creation of Ignácio de Loyola Brandão for "Não Verás". We ahserved, in the third chapter, the behaviour of different lanquages (visual, musical, cinematographic, journalistic and verbal) when they enconter during the pregnancy of this specific creation. In the lastl chapter, the birth of "Não Verás" is analysed in its literary materalization - how the literary elements werei built up ouring the process. Finally, we present the conclusion we reached about the proceeding of the artistic process of creation after our immersiun in the creative world of Loyola